Isotopic analysis of sulphur in the assessment of SO2 emission sources - Beričnik-Vrbovšek, Julija (Acta chimica slovenica, 2002)
Reported herein is the isotopic composition of sulphur in Norway spruce needles, lichens and soils from two well-defined climatic regions in Slovenia:the Šalek Valley and the Yasavje region. The samples are from distinct locations in these regions, where the impact of SOsub2 on vegetation is well documented. In both regions, the main source of SOsub2 pollution is from thermal power stations. The isotopic measurements of Norway spruce needles were complemented with Rosup34 S-analyses of coals (lignite and brown coal) and SOsub2 in stack-gases from two thermal power plants, to correlate SOsub2 pollution with a specific emission source. Reference samples od SOsub2 form an unpolluted region (The Triglav national park) werecollected for comparison. To elucidate the turn over of SOsub2 from source to spruce needles via air and /or soil, characterustic soils and lichens (Hypogymnia psychodes) were sampled. The sulphur in the samples was converted by combustion in a small oxygen bomb (Parr instrument) to sulphate, precipitated as BaSO and the Rosup31S values measured using an isotope ratiomass spectrometer coupled on-line to an elemental analyser. The Rosup31S values demonstrate only a close relationship between environmental SOsub2 and lichens. Correlation between a particular emission source and theapparent impact on vegetation from the Rosup34S values is not straightforward.
Keywords: analizna kemija; ecology; ekologija; emisije; izotopske analize; kemijska analiza; lišaji; onesnaževanje okolja; žveplo; žveplov dioksid